Behavior of resin composites at the interface between orthodontic bracket and tooth - Bangalore Huchaiah, Durgesh (fi=Turun yliopisto|en=University of Turku|, 2019)
Adhesive interface between bracket and enamel is based on adhesion of resin-based material to enamel and to bracket, the latter being typically reinforced by mechanical retention of the bracket bonding surface. Bonding results are influenced by brackets, adhesive systems and by composite resin between bracket and enamel. The adhesion strength is also influenced by use of possible reinforcing materials at the interface. The main objective of this study was to study the behavior of resin composites at the bracket-tooth interface under different loading conditions with or without use of intermediate layers of reinforcing glass fibers. The orthodontic brackets were bonded using flowable composites with different visco-elastic properties and the values of debonding load and displacement were determined at the point of debonding. The degree of cure (DC %) of the glass fiber reinforced adhesive layer underneath the bracket and irradiance power of the light curing tip underneath the bracket was determined. Furthermore, the creep behavior of the interface adhesive materials was studied using orthodontic bracket-tooth and three-point bending test models. The adhesive interface was subjected to constant interfacial loading. To characterize the properties of the adhesive interface materials used, nanomechanical (nanohardness and elastic modulus) properties was evaluated. The outcome of the experimental study demonstrated that the incorporation of a glass-fiber reinforced composite (FRC) with a low elastic modulus at the adhesive interface between the orthodontic bracket and enamel increased the debonding force and strain compared to adhesive systems with higher elastic modulus. An enhanced degree of cure of the photopolymerizable adhesive reinforced with glass FRC was observed under the metal brackets. The creep test demonstrated that the incorporation of continuous glass fibers at the interface between orthodontic bracket and enamel increased the creeping and debonding time of the bracket and that the orientation of the fibers and the resin matrix type significantly affected the creep behavior of the adhesive materials. From the above outcome, it can be concluded that incorporation of glass FRC at the adhesive interface could be beneficial considering the long duration of orthodontic brackets remaining in the oral cavity.

Oikomishoidon brakettien ja hampaan välissä olevan yhdistelmämuovin käyttäytyminen Hampaiden oikomishoidossa käytettävät kiinnikkeet, ns. braketit liimataan hampaan kiillepintaan. Liimasauman kestävyys riippuu hampaan pinnan käsittelystä ja liima-aineen koostumuksesta. Tämän väitöskirjatutkimuksen tarkoituksena oli selvittää braketin ja hampaan välisen liimasauman käyttäytymistä erilaisissa kuormitustilanteissa ja tilanteissa, joissa liiman koostumusta muutettiin muun muassa lisäämällä siihen lasikuitukomposiittia. Brakettien liimaamisessa käytettiin liimoja, joiden visko-elastiset ominaisuudet poikkesivat toisistaan, jonka takia niiden käyttäytyminen kuormitustilanteessa vaihteli, mikä olikin yksi tutkimuksen kohde. Liima-aineen kovettumista tutkittiin mittaamalla liima-aineen monomeerien reagoimista keskenään, eli niin sanottua kovettumisastetta (degree of monomer conversion, DC%) ja koska kovettumisreaktio käynnistetään valolla, selvitettiin lasikutujen mahdollista vaikutusta valon kulkeutumiseen braketin ja hampaan väliseen tilaan. Kliinisesti liimasaumaan kohdistuvaa kuormitustilannetta jäljitettiin pitkäkestoisella staattisella kuormitustestillä, jossa liima-aineen polymeerirakenteen viruminen (creeping) määritettiin erilaisille liimakoostumuksille. Liima-aineet tutkittiin myös niiden nanomekaanisten ominaisuuksien suhteen määrittämällä pinnan nanokovuus ja kimmoisuusmoduuli. Tutkimuksen tulokset osoittivat, että itse liima-ainetta alhaisemman kimmoisuusmoduulin lasikuitukomposiitin käyttäminen braketin ja hampaan rajapinnassa lisäsivät kiinnitysvoimaa ja rajapinnan muodonmuutoksen määrää kuormituksessa. Lasikuitujen avulla pystyttiin lisäksi parantamaan liiman kovettumista kovetusvalon avulla. Mielenkiintoinen tutkimustulos liimasauman käyttäytymisestä pitkäaikaisessa kuormitustuloksessa liittyi myös lasikuituihin: lasikuitujen suunnalla suhteessa kuormittavan voimaan suuntaa oli vaikutusta liimasauman virumiseen ja braketin irtoamiseen hampaan pinnasta. Yhteenvetona tutkimustuloksista voidaan todeta, että lasikuitukomposiitin käyttämisellä oikoimishoidon braketin ja hampaan välissä voidaan vaikuttaa liimasauman kuormituskestävyyteen ja sillä voi olla kliinisesti merkittävää hyötyä.